Investigation of a non-explosive directional roof cutting technology for self-formed roadway - Zhang, Quan; He, Manchao; Wang, Jiong; Guo, Shan; Zhu, Chun; Tao, Zhigang; Wang, Chao (International journal of mining science and technology, 2022)
Traditional explosives have characteristics of high risk, large vibration, and poor directional fracturing. Consequently, an instantaneous expander with a single crack surface (IESCS), which is a novel non-explosive directional rock-breaking technique, has been developed. The directional roof-cutting mechanism of the IESCS method, driven by high-pressure gas, was theoretically analyzed. Laboratory experiments and numerical simulations proved the directional slitting effect of the IESCS method to be excellent. Compared with shaped-charge blasting, the charge of IESCS was reduced by 8.9%, but the crack rate increased by 9% in field tests. After IESCS pre-splitting, the roof directionally collapsed along the cutting line, and the gangue filled the goaf. Moreover, the directional roof cutting by the IESCS could decrease roadway stress. The average pressure of hydraulic supports on the cutting side of the roof was 31% lower than that on the non-cutting side of the roof after pre-splitting. After the self-formed roadway constructed by the IESCS was stabilized, the final relative displacement of the roof and floor was 157.3 mm, meeting the required standard of the next working face. Thus, the IESCS was effectively applied to directional roof pre-splitting. The results demonstrate the promising potential of IESCS in the mining and geotechnical fields.